Studies of lithium deposition and D retention on tungsten samples exposed to Li-seeded plasmas in PISCES-A. (22nd February 2017) - Tabarés, F L; Alegre, D; Baldwin, M; Nishijima, D; Simmonds, M; Doerner, R; Alves, E; Mateus, R
Abstract: The interaction between lithium-seeded deuterium plasmas and tungsten targets has been studied in the PISCES-A divertor plasma simulator. Tungsten samples, of ITER-grade, with a diameter of 25 and 2 mm thick, were held at temperatures ranging from 403 to 873 K and exposed to Li/D plasmas under different plasma conditions and fixed total fluences of 5 ×10 25 m −2, with typical particle flux values of (1–5) × 10 22 m −2 s −1 . The deuterium and lithium contents of the samples after irradiation were analyzed by thermal desorption spectroscopy and nuclear reaction analysis (NRA). No lithium deposition was found within the sensitivity range of NRA, except for the cold (403 K) sample on which a layer with Li atomic density below 2 × 10 22 m −2 was detected. Deuterium retention values in the range of 10 18 m −2 were measured, even for the Li deposition conditions.